The effect of machining parameters on surface integrity of mild steel material using lathe machine / Faiz Azzhar Hamzah - Hamzah, Faiz Azzhar (2022)
In this era, the use of mild steel material has been widely marketed. Because of its strength, low cost, easy to get and machinability. However, the industry has problems in developing smooth surface mild steel products by using lathe machine for everyday usage. So, in this study, we investigate the relation of the machining parameters can affect the surface integrity of mild steel. Depth of cut, speed rate and feed rate are used. It also to analyse surface integrity of mild steel material. The purpose of the research is to help student or new users of lathe machine about how to produce smooth surface products that use mild steel materials. The method that we use in this project is turning process. After evaluating the results obtained, variance and regression analyses were performed. Based on the analysis of variance, for general purpose machining, use a recommended feed rate of 0.254 mm/min, cutting speed is 550rpm and the depth of cut for mild steel is (0.5-1.0) mm. The method that we use to measure surface roughness by using Ra and RMS calculation. Conclusion is, this project will be very helpful and useful for student and new comers in this industries, because this study will guide them to use the lathe machine properly. It also able to avoid losses to companies related to the manufacture of materials in terms of money and their time.